Technological change, fuel efficiency and carbon intensity in electricity generation: A cross-country empirical study - Elena Verdolini; Nick Johnstone; Ivan Hascic (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper provides an empirical analysis of the determinants of energy efficiency in fossil fuel electricity generation across 28 OECD countries over the period 1981-2006, with particular attention to the role played by technological development and the availability of energy efficient technologies in the market. This contribution is novel in three respects: first, empirically assess the effects of different determinants of energy efficiency, which include the input mix in electricity generation, the capacity ratio at which power plants are run, as well as the characteristics of the production technology. Second, we focus on the role of technological availability: using patent data for carefully selected innovations in fossil-fuel technologies, we build an indicator which proxies for technological developments in fuel-efficient electricity generation. Third, by formalizing the relationship between fuel efficiency and carbon intensity, we assess the impact of changes in the input mix and in technological availability on CO2 emissions in the electricity sector. Results show that input mix, capacity utilization and new investment in capacity play a significant role in increasing energy efficiency. Increasing the stock of available technologies (or stock of knowledge) is also associated with higher efficiency levels. Given the link between increased efficiency and lower CO2 emissions, we conclude that technological change has a negative and significant effect on carbon intensity, while the changing input mix affects CO2 intensity both through an increase in efficiency as well as by lowering the input-weighted emission factor.
Keywords: Q40; O33; O13; 330; Fossil Fuel Electricity Generation; Energy Efficiency; Carbon Intensity; Technological Change; Patents